Assessment of the Impact of Electric Power Production on the Economic Growth of Kazakhstan - Smagulova, Sholpan; Chereyeva, Bakhytgul; Zhakupova, Saltanat; Intykbayeva, Saule; Abdulina, Bayan; Sarzhanov, Taizhan; Abdulina, Gulnar; Abeldanova, Aigerim (International Journal of Energy Economics and Policy, 2024)
This scientific research is devoted to the analysis of the impact of the development of the energy industry on economic growth in Kazakhstan. The work assesses the economic development of the country using the example of a comparative analysis of the state of the GDP level from 2011 to 2023. Particular emphasis is placed on increasing industrial production of finished goods. It stands out here that to ensure economic growth, the rapid pace of development of the domestic energy sector is not enough. The study emphasizes that electricity generation mainly comes from thermal power plants using coal. There is a high level of equipment depreciation and wear and tear, which leads to significant harmful emissions, delivery losses and a decline in electricity generation. Some attention is paid to intensifying the construction of renewable energy sources. Here, an economic and mathematical model was built and forecasting was implemented in order to determine the factors affecting the growth of electricity generation in Kazakhstan. To solve energy shortage issues and achieve economic growth, an investment mechanism is proposed using the example of PPP infrastructure energy projects. In order to enhance the influx of investment in the reconstruction and construction of new Kazakh energy facilities, mutually beneficial cooperation between the state and business within the framework of PPP approaches is justified. Key problems are identified and measures for economic growth and stimulation of development of the energy complex are proposed. It is recommended to intensify investments in the construction of nuclear power plants, new renewable energy facilities and innovative power plants.